1992
DOI: 10.1126/science.1546323
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Motor Impairments Associated with SIV Infection in Rhesus Monkeys

Abstract: Cognitive and motor deficits are now recognized as significant clinical features of infection with the human immunodeficiency virus (HIV). Juvenile rhesus macaques infected with simian immunodeficiency virus (SIV) were found to exhibit cognitive and motor deficits characteristic of HIV infection. Impairment on a motor skill task was the most reliable indicator of infection. Various cognitive impairments were also evident. These deficits were related to SIV infection of the brain but not to inflammatory lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(90 citation statements)
references
References 17 publications
4
85
0
1
Order By: Relevance
“…CNS disease in HIV infection frequently is associated with psychomotor slowing as well as impaired fine and gross motor function (12,13,16). In a study of cognitive and motor impairment in SIV-infected rhesus monkeys, motor skills were the most consistent impairment found (21,39). We also have found that SIV infection can result in transient periods of poor performance over the course of infection as well as sustained abnormalities in the later stages of disease (23).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…CNS disease in HIV infection frequently is associated with psychomotor slowing as well as impaired fine and gross motor function (12,13,16). In a study of cognitive and motor impairment in SIV-infected rhesus monkeys, motor skills were the most consistent impairment found (21,39). We also have found that SIV infection can result in transient periods of poor performance over the course of infection as well as sustained abnormalities in the later stages of disease (23).…”
Section: Discussionmentioning
confidence: 93%
“…SIV has been shown to cause an AIDS-like immune deficiency and CNS infection when inoculated into rhesus monkeys (19,20). We and others have demonstrated functional CNS deficiencies in SIV-infected rhesus monkeys, including abnormalities in sensory-evoked potentials, behavioral͞cognitive abnormalities, and motor problems (21)(22)(23). Here we focus on the examination of multiple physiological parameters during the early states of SIV infection of rhesus monkeys.…”
mentioning
confidence: 99%
“…Disruptions in progressive-ratio performance measured in short probe sessions result from decreases in overall rates of responding and can be interpreted to reflect both motor slowing and a reduction in motivation to work for food. Cognitive and motor impairments have also been reported in monkeys infected with a different strain of SIV (31). A convergence of evidence from electrophysiological and neuropsychological measurements will help to fully characterize the neurological changes associated with SIV infection.…”
Section: Infiltrating T Cellsmentioning
confidence: 99%
“…The cognitive tasks were as follows: (1) delayed matching-to-sample with new stimuli on every trial to test visual recognition memory; (2) delayed matching-to-sample with two repeatedly used stimuli to test recent memory, (3) a visual discrimination learning and retention task to test stimulus-response association, and (4) a spatial scene learning task, which measured long-term memory for spatial locations. The motor task assessed the ability of each monkey to retrieve food from a rotating table (via the turntable speed at which animals successfully retrieved food in 50% of trials) [41].…”
Section: Development Of the Siv Animal Modelmentioning
confidence: 99%
“…The tasks were selected for their breadth in capturing neuropsychological impairments, including those described in HIV-infected humans, and for their ability to target neural substrates well characterized in primate lesioning experiments and implicated in HAD [41,37]. The tasks assessed cognitive and motor function.…”
Section: Development Of the Siv Animal Modelmentioning
confidence: 99%